Assessing the impact of COVID-19 on epidemiological changes of severe pediatric respiratory syncytial virus infections in Malaysia - Chan, Chee Mun; Wahab, Asrul Abdul; Ali, Adli (Frontiers in Public Health, 2024)
Introduction Respiratory syncytial virus (RSV) is one of the leading causes of hospitalization and mortality among children with respiratory tract infections. The non-pharmaceutical preventive measures against severe acute respiratory syndrome coronavirus (COVID-19) may have reduced the transmission of RSV, altering its tropical epidemiological seasonality. Thus, this study represents the first attempt to evaluate changes in RSV epidemiology in the context of COVID-19 pandemic in Malaysia. Methods Conducted at a tertiary hospital in Kuala Lumpur, Malaysia, this retrospective study analyzed collated data of children aged <12 years who were admitted for severe respiratory infections from 2017 to 2022. Time series models were used to predict the differences between actual and forecasted RSV cases, while logistic regression assessed the statistical association between RSV and COVID-19. Results Among the 4,084 children analyzed, we reported a significant inverse relationship between RSV and COVID-19 infections during the pandemic (2020–2021) (p < 0.05). In 2020, the RSV positivity rate sharply declined to 8.3 and 5.9%, respectively, in the two prominent seasons. Time series analysis showed a tremendous decrease in cases compared to the expected values, with reductions of 98.3% in the first season and 95.7% in the second season. However, following the lifting of the restriction order in 2022, RSV infections rose sharply with a positivity rate of 36.3%, higher than pre-COVID-19 pandemic levels. Conclusion This study provides evidence of increasing RSV cases post-COVID-19 pandemic, due to immunity debt. Hence, the healthcare system must be prepared to address future RSV outbreaks with the appropriate implementation of prophylaxis and public health measures.